Ecotourism in Eaglesnest, West Kameng, Arunachal Pradesh: A Case Study - Lobo, Peter (Atna Journal of Tourism Studies, 2012)
This study was aimed at exploring tourism resources and Ecotourism behaviour of tourists and local people to provide guidelines for Ecotourism development of Eaglesnest, West Kameng, Arunachal Pradesh. Tourists were selected by applying the method of convenience sampling, wherein, local people were interviewed in depth to gather local information. Results of the research showed that Eaglesnest had an outstanding tourism resource which was Bird watching, especially after the discovery of the new species of bird to the world, which is known as Bugun Liochicla, which attracted tourists from all over the world. Most of the tourists received tourism information from trip reports and advertising. They were normally grouped visitors who visited the destination for wildlife, especially Bird watching. On an average, they stayed over seven nights at different campsites. Nearly all tourists were aware of Ecotourism. The most attractive resource was Bird watching. They also admired the landscapes, the scenery of the forest and mountains